Transformative Islamic Education through Cultural Traditions: A Case Study of the Haul of Ki Ageng Tarub - Sariyani Sariyani; Rafael Humberto Pinzon (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2025)
This study seeks to explore the transformative Islamic educational values ​​manifested in the Haul Ki Ageng Tarub tradition and its contribution to the formation of the Islamic character of the younger generation within the framework of the Golden Indonesia 2045 vision and Sustainable Development Goal (SDG) 4. This study employed qualitative methods with an educational ethnography approach, conducted in Tarub Village, Grobogan, Central Java. Data were obtained through participatory observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles and Huberman. The results confirm that the Haul Ki Ageng Tarub tradition serves as a transformative non-formal Islamic educational vehicle, where the learning process occurs naturally through experience, social interaction, and cross-generational role models. Religious values ​​are reflected in tahlil (remembrance of God), dhikr (remembrance of God), communal prayers, and religious studies, which foster spiritual and social awareness. Social solidarity is fostered through the practice of mutual cooperation (gotong royaong), almsgiving, and active community participation. Meanwhile, the preservation of local culture is realized through shadow puppet performances, which are imbued with Islamic moral messages. The synergy between spirituality and local culture demonstrates the inclusive and moderate face of Islam in the Indonesian archipelago. Therefore, the Haul Ki Ageng Tarub tradition can be viewed as a social laboratory for Islamic character education, supporting the realization of quality, culturally rooted, and sustainable education, as mandated by SDGs 4, and serving as a crucial foundation for achieving the vision of Indonesia Emas 2045.